Coping Well with Advanced Cancer: A Serial Qualitative Interview Study with Patients and Family Carers - Walshe, Catherine (PLoS One, 2017)
OBJECTIVES: To understand successful strategies used by people to cope well when living with advanced cancer; to explore how professionals can support effective coping strategies; to understand how to support development of effective coping strategies for patients and family carers. DESIGN: Qualitative serial (4–12 week intervals) interview study with people with advanced cancer and their informal carers followed by focus groups. The iterative design had a novel focus on positive coping strategies. Interview analysis focused on patients and carers as individuals and pairs, exploring multiple dimensions of their coping experiences. Focus group analysis explored strategies for intervention development. PARTICIPANTS: 26 people with advanced (stage 3–4) breast, prostate, lung or colorectal cancer, or in receipt of palliative care, and 24 paired nominated informal/family carers. SETTING: Participants recruited through outpatient clinics at two tertiary cancer centres in Merseyside and Manchester, UK, between June 2012 and July 2013. RESULTS: 45 patient and 41 carer interviews were conducted plus 4 focus groups (16 participants). People with advanced cancer and their informal/family carers develop coping strategies which enable effective management of psychological wellbeing. People draw from pre-diagnosis coping strategies, but these develop through responding to the experience of living with advanced cancer. Strategies include being realistic, indulgence, support, and learning from others, which enabled participants to regain a sense of wellbeing after emotional challenge. Learning from peers emerged as particularly important in promoting psychological wellbeing through the development of effective ‘everyday’, non-clinical coping strategies. CONCLUSIONS: Our findings challenge current models of providing psychological support for those with advanced cancer which focus on professional intervention. It is important to recognise, enable and support peoples’ own resources and coping strategies. Peer support may have potential, and could be a patient-centred, cost effective way of managing the needs of a growing population of those living with advanced cancer.